Anatomy and Physiology : Therapy basics - McGuinness, Helen (London : Hodder & Stoughton, 2002)
This workbook concentrates on the basic knowledge required for NVQ/SVQ Levels 2 and 3. The major features are the tasks and self-assessment questions which, when complete, will make up an important part of students' folios.
Previous ed.: 1995.
Includes bibliographical references (p. 324) and index.
Keywords: Anatomy; Anatomy -- Problems, exercises, etc; Physiology; Physiology -- Problems, exercises, etc; Health and Fitness